2023
DOI: 10.1038/s41409-023-01944-2
|View full text |Cite
|
Sign up to set email alerts
|

CMV-IgG pre-allogeneic hematopoietic stem cell transplantation and the risk for CMV reactivation and mortality

Abstract: Cytomegalovirus (CMV) represents one of the most common infectious complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Currently, a common diagnostic test used to stratify the risk for CMV infection in allo-HSCT recipients is the qualitative CMV serology of donor and recipient. A positive serostatus of the recipient is the most important risk factor for CMV reactivation and associated with reduced overall survival post-transplantation (TX). Direct and indirect effects of CMV are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…According to this evidence, lower TTV‐DNA levels shortly after engraftment were already reported in allo‐HSCT recipients developing a high‐level CMV DNAemia 24 . Furthermore, in accordance with previous observations, a CMV‐positive serostatus of the recipient was correlated with a poorer prognosis in our cohort 32,33 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to this evidence, lower TTV‐DNA levels shortly after engraftment were already reported in allo‐HSCT recipients developing a high‐level CMV DNAemia 24 . Furthermore, in accordance with previous observations, a CMV‐positive serostatus of the recipient was correlated with a poorer prognosis in our cohort 32,33 …”
Section: Discussionsupporting
confidence: 91%
“…24 Furthermore, in accordance with previous observations, a CMV-positive serostatus of the recipient was correlated with a poorer prognosis in our cohort. 32,33 In our cohort a limited number of patients showed no or first CMV reactivation/infection.…”
Section: Discussionmentioning
confidence: 86%
“…Our data only relate to viral replication at a particular moment and does not reflect the number of reactivations that each patient may have experienced. To better address this question, we measured anti-CMV IgG titers because high titers were associated with a higher risk of developing CMV reactivation ( 35 , 36 ). We demonstrated that higher titers were associated with enrichment of T 8 sen, suggesting repetitive immunological stimulation by CMV in T 8 sen high patients.…”
Section: Discussionmentioning
confidence: 99%
“…Median age across all cohorts included in the clinical analysis was 63. 35 (31.50 to 92.86) years old. Patients had a median of 2 (0 to 7) metastatic sites.…”
Section: Introductionmentioning
confidence: 99%
“…In a single-center 13-year cohort study, we reviewed the impact of pretransplant CMV IgG titers on CMV replication during the first 180 days posttransplant in 422 allogeneic HCT CMV Rþ (294 Dþ/Rþ and 128 DÀ/Rþ). The median Additional data from an elaborate discovery and validation cohort study were recently presented at the 50 th annual meeting of the European Bone Marrow Transplant (EBMT) Society by the Seattle group [8]. Pretransplant sera from 478 allogeneic HCT DÀRþ patients between 2007 and 2017, before the introduction of letermovir in clinical practice, were tested for CMV-specific humoral immunity by display immunoprecipitation and sequencing (Vir-Scan).…”
Section: Key Pointsmentioning
confidence: 99%